Growth curves, time of thinning and prevision of final size of the fruit on three peach cultivars - Pereira, José Francisco Martins; Feliciano, Ascunia Jimenez; Raseira, Maria do Carmo Bassols; Silva, João Baptista da (Pesquisa Agropecuaria Brasileira, 2014)
Peach cultivars (Prunus Persica (L.) Batsch) Diamante, Capdeboscq and Magno, classified in maturation period as early, mid-season to late and late, respectively, were used in the present study. The time of thinning was 30 days after blooming, begining of pit harding and pit hard stage. Time of thinning did not alter the duration of the three stages of fruit growth and significantly affected fruit diameter only of cv. Magno, when thinning was done at the third period. Duration of the first and third stages of fruit growth were similar for the three cultivars despite the time of thinning. Pronounced differences, however, were obtained in the second stage, which was shortest for the Diamante and longest for the cultivar Magno. There was a significant correlation between sire of fruit early in the season and fruit size at harvest; however, fruit size prediction was more accurate when done close to harvest.